2014
DOI: 10.4162/nrp.2014.8.4.368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lycopene on number and function of human peripheral blood endothelial progenitor cells cultivated with high glucose

Abstract: BACKGROUND/OBJECTIVESThe objectives of this study were to investigate the effects of lycopene on the migration, adhesion, tube formation capacity, and p38 mitogen-activated protein kinase (p38 MAPK) activity of endothelial progenitor cells (EPCs) cultivated with high glucose (HG) and as well as explore the mechanism behind the protective effects of lycopene on peripheral blood EPCs.MATERIALS/METHODSMononuclear cells were isolated from human peripheral blood by Ficoll density gradient centrifugation. EPCs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Moreover, it has been shown that vascular endothelial dysfunction and the number of endothelial progenitor cells (EPCs) are important risk factors for the development of vascular complications in T2DM. Zeng et al [ 108 ] reported that lower cell proliferation, migration, adhesion, and in vitro vasculogenesis capacity, as well as increased EPC’s apoptosis, were observed in the high glucose rats group. Lycopene treatment inhibits high glucose-induced EPC injury by inhibiting ROS generation and downregulating phosphorylation of p38 mitogen-activated protein kinases (p38 MAPK).…”
Section: Mechanisms Of Action Of Lycopene In T2dmmentioning
confidence: 99%
“…Moreover, it has been shown that vascular endothelial dysfunction and the number of endothelial progenitor cells (EPCs) are important risk factors for the development of vascular complications in T2DM. Zeng et al [ 108 ] reported that lower cell proliferation, migration, adhesion, and in vitro vasculogenesis capacity, as well as increased EPC’s apoptosis, were observed in the high glucose rats group. Lycopene treatment inhibits high glucose-induced EPC injury by inhibiting ROS generation and downregulating phosphorylation of p38 mitogen-activated protein kinases (p38 MAPK).…”
Section: Mechanisms Of Action Of Lycopene In T2dmmentioning
confidence: 99%
“…[ 37–44 ] It was also stated that lycopene was effective in regulating blood sugar, insulin, and insulin intolerance by inhibiting STAT3 signaling. [ 45,46 ] There are also in vitro studies on lycopene, but they are mostly focused on cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…intolerance by inhibiting STAT3 signaling. [45,46] There are also in vitro studies on lycopene, but they are mostly focused on cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…35 Lycopene has a good antioxidant activity, especially against oxygenderived radicals and has the highest singlet oxygen quenching capability among all carotenoids in biological systems. 18,22 The large number of conjugated double bonds in lycopene makes it a potent antioxidant because the delocalization of π electrons that occurs along the double bond allows the neutralization reaction of molecules containing unpaired electrons. 19,35 The radical neutralization reaction of lycopene can occur in various ways, including adding radicals to the polyene chain, electron transfer from lycopene to radicals, or eliminating hydrogen atoms from lycopene.…”
Section: Lycopene Ameliorates Oxidative Stress In Dmmentioning
confidence: 99%
“…Many studies have shown that lycopene shows potential beneficial effects in cancer and lifelong diseases, such as cardiovascular, neurodegenerative, and metabolic diseases which includes diabetes. [20][21][22] In vitro and in vivo studies show that lycopene has potential in diabetes therapy and prevention of disease progression associated with diabetes complications but have not yet explained its molecular mechanism in detail. Therefore, this literature review was made to summarize the results of studies (see Tables 1-4) related to the beneficial effect of lycopene in DM in the last decade and highlight several important molecular pathways (see Figure 1) involved such as oxidative stress, inflammation (nuclear factor-kappa B [NF-κB] pathway), insulin signaling (phosphatidylinositol 3-kinase [PI3K]/AKT pathway), apoptosis, and autophagy.…”
Section: Introductionmentioning
confidence: 99%